Do bank bondholders price banks' ability to manage risk/return?. Issue 44 (20th September 2018) - Casteuble, Cécile; Nys, Emmanuelle; Rous, Philippe
ABSTRACT: In this paper, we empirically investigate whether bank bondholders value risk management, measured as risk-return efficiency (RRE), when pricing bond spreads. Based on a sample of 2, 452 bonds issued by 78 European listed banks, for the period 2001–2015, we find evidence that the ability of banks to manage risk affects bond spreads: banks with more capable managers obtain a lower cost of debt. In particular our results show that bank bondholders are even more sensitive to RRE during the crisis period, for relatively poorly rated bonds, for unsecured/subordinated debt, and for long maturity debt. Our findings highlight that bondholders' monitoring of banks is effective and takes into account the efficiency of risk management during financial and economic downturns, but during sound periods bank bondholders should strengthen their monitoring of risk management.